Terbinafine Induced Acute Generalized Exanthematous Pustulosis Treated with Adalimumab: Recalcitrant to Systemic Corticosteroid Therapy - Deng L; He B; Ali K; Bu Z (Clinical, Cosmetic and Investigational Dermatology, 2023)
Lin Deng,1 Beilei He,2 Kamran Ali,1,3 Zhangyu Bu1 1Department of Dermatology Affiliated Hangzhou First People’s Hospital, Zhejiang University School of Medicine, Hangzhou, People’s Republic of China; 2Department of the Fourth Clinical Medical College, Zhejiang Chinese Medical University, Hangzhou, People’s Republic of China; 3Department of Dermatology, International Education College of Zhejiang Chinese Medical University, Hangzhou, People’s Republic of ChinaCorrespondence: Zhangyu Bu, Department of Dermatology, Affiliated Hangzhou First People’s Hospital, Zhejiang University School of Medicine, No. 261, Huansha Road, Hangzhou, People’s Republic of China, Tel +8657156006617, Email buzyhz@163.comAbstract: Acute generalized exanthematous pustulosis (AGEP) is generally caused by drugs and is characterized by the rapid development of numerous non-follicular sterile pustules on an erythematous base, fever, and neutrophilia. We report an association between terbinafine, with AGEP, and adalimumab treatment. A 24-year-old teenage female patient with a history of onychomycosis was treated with terbinafine. On the second day of the first dose, multiple edematous and erythematous lesions appear with pinhead pustules. Neutrophilia was observed in the blood report. The clinical history, lesions, and laboratory evaluations were consistent with AGEP. We discontinued the terbinafine therapy, and the systemic corticosteroid was initiated; however, the patient’s condition worsened. Adalimumab subcutaneously was initiated, and the symptoms cleared up in weeks. The European Study of Severe Cutaneous Adverse Reactions (EuroSCAR) scoring system and Naranjo’s algorithm scale were used to check the possibility of a drug-induced adverse reaction. The Association of AGEP with the terbinafine drug is not rare. However, there are no reports or literature of drug-related rash or exanthematous eruptions unresponsive to corticosteroids and treated with adalimumab.Keywords: acute generalized exanthematous pustulosis, AGEP, adalimumab, terbinafine, drug-induced adverse reaction, Naranjo’s algorithm scale, EuroSCAR